Ayur-Panchagavya Therapy For Thyroid Disorders With Special Reference To Hypothyroidism-An Anukta Vyadhi - Rao A, Babitha; DP, Ramesh (International Research Journal of Ayurveda & Yoga, 2021)
Panchgavya, a term used to describe five major substances obtained from indigenous inbreed cow Gomutra(urine), Gomaya(dung), Ksheera(milk), Dadhi(curd), Gritha (ghee). Ayur-Panchagvya, term used to denote panchagavya along with kasta and Rasa Aushadhi. Ancient Ayurvedic literature and recent research proves high medicinal value. Anukta vyadhi’s are to be understood by Yukti and assessing Nidana panchaka; features of Hypothyroidism fall under Galaganda, Shotha(inflammation), Pandu(anaemia), Kshaya (debility) etc but not directly mentioned. Only treatment being hormone replacement therapy, opens up wide gateway for clinical research for achieving normal functionality of gland. Panchagavya therapy, Nidana parivarjana, healthy life style provides promising results with phyco-somatic symptomatic improvements and normalizing lab reports. Its mains principle being Apatarpana and bruhmana vyatyasa chikitsa. Upon observation the patients were either completely cured or show stable gland functions. The effect of treatment can be boosted with Prabhava of Daivavyapasharaya chikitsa. Along with positive effects there were few minor adverse effects like burning micturition, which was easily combated with sheeta upachara (cold therapy). Though at broader level this positive prognosis can be justified, need more detailed study in further days for establishment of standardised protocol.